Ascèse sportive et mode de vie communautaire : le quotidien de sportifs de haut niveau en athlétisme - Sylvaine Derycke (L'Atelier du CRH)
Sport asceticism and community life style: the everyday life of elite athletes.The survey takes place in a national elite athletes center called the ‘ National Institut of Sport and Physical Education ‘(INSEP). Its functionning shows many similarities with monastic life which allows us to look at it as a “practiced utopia”. A form of asceticism seems to be the means to achieve this new utopia. Its is seen as the framework from which interpersonal relationships are created or drift apart. The approach consists in understanding the connivance between sport environment and religious sphere in order to envision the implicit power of the Judaeo-Christian heritage that has been reactivated by contemporary logics and to truly size up the potential of renewing and displacing faith productions.